Water quality assessment in the Gorky Reservoir (Volga River, Russia) based on biotesting and chemical analysis - Tomilina I.I.; Lozhkina R.A.; Gapeeva M.V. (Трансформация экосистем)
In 2010–2022, the toxicological characteristics of the Gorky Reservoir waters were studied using the biotesting method with the cladoceran Ceriodaphnia dubia Richard, 1894. A statistically significant decline in the fecundity of crustaceans in the lake section (regardless of the year of observation), compared to the river part of the reservoir, was recorded. The chemical composition of the surface waters of the Gorky Reservoir in September 2015 was distinguished by the excess of the maximum permissible concentration established for fishery (MPCfish), i.e. for Cu (16.8–38.3) and Zn (1.1–3.4). Their peak concentrations (38.3 and 3.4, respectively) were detected at the Sezema River station. Downstream, a gradual increase (by1.1–3.5 times) in concentrations of Sr, Mo, Si, As and V occurred, being maximum at the dam section. During the observation period, a tendency towards a decrease in the average toxicity index was noted for the reservoir as a whole. Unlike other sites, the lake section of the reservoir (regardless of the year of observation) demonstrated a statistically significant reduction in the crustacean fecundity. This was due to water contamination, as evidenced by the results of correlation analysis and the presence of higher concentrations of the studied chemicals in sampling stations located within this section.